2021
DOI: 10.3389/fimmu.2021.688364
|View full text |Cite
|
Sign up to set email alerts
|

Case Report and Review of the Literature: Bullous Skin Eruption After the Booster-Dose of Influenza Vaccine in a Pediatric Patient With Polymorphic Maculopapular Cutaneous Mastocytosis

Abstract: Vaccination is a well-known trigger for mast cell degranulation in subjects affected by mastocytosis. Nevertheless, there is no exact standardized protocol to prevent a possible reaction after a vaccine injection, especially for patients who have already presented a previous vaccine-related adverse event, considering that these patients frequently tolerate future vaccine doses. For this reason, we aim to share our experience at Meyer Children’s University Hospital in Florence to raise awareness on the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The National Institutes of Health conducted a retrospective chart review of 94 children with mastocytosis who received 2136 vaccines, finding that 4% of children had urticaria, anaphylaxis, and exacerbated skin lesions [23]. Case studies have reported children developing bullous skin eruptions and a mastocytoma at the site of vaccination [44,48,49]. The frequency and severity of mast cell activation and adverse reactions to vaccines is higher in pediatric mastocytosis patients with greater skin involvement, diffuse cutaneous mastocytosis, and elevated basal serum tryptase [44,50].…”
Section: Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Institutes of Health conducted a retrospective chart review of 94 children with mastocytosis who received 2136 vaccines, finding that 4% of children had urticaria, anaphylaxis, and exacerbated skin lesions [23]. Case studies have reported children developing bullous skin eruptions and a mastocytoma at the site of vaccination [44,48,49]. The frequency and severity of mast cell activation and adverse reactions to vaccines is higher in pediatric mastocytosis patients with greater skin involvement, diffuse cutaneous mastocytosis, and elevated basal serum tryptase [44,50].…”
Section: Vaccinesmentioning
confidence: 99%
“…Children with cutaneous mastocytosis are often advised to avoid a variety of medications including NSAIDs, antibiotics, RCM, and vaccines. There are few case reports describing adverse reactions in children with mastocytosis although antibiotics and vaccines have both been reported [44,48,96].…”
Section: Drug Hypersensitivity In Children and Pregnant Womenmentioning
confidence: 99%
“…Data from the literature mainly refer to children with CM, which is the most common type in this age group. Most studies have been conducted on small groups of patients, while severe VARs occur only as case reports (20,23,24) . Some studies have reported a higher incidence of adverse reactions in paediatric patients with all types of mastocytosis…”
Section: Prophylactic Vaccinationmentioning
confidence: 99%
“…Vaccines for infectious diseases may trigger MC mediator release in patients with mastocytosis, but the rate of such HRs is unknown. In small population samples, vaccines have been reported to trigger adverse reactions in 6–13% of children with mastocytosis [ 71 , 72 , 73 ]. According to National Institute Health (NIH) retrospective data, the incidence of adverse reactions to vaccination was 1.8% and the prevalence 8% in 75 children with mastocytosis [ 1 ].…”
Section: Vaccines For Infectious Diseasesmentioning
confidence: 99%